Teachers’ and principals’ experiences with assessing Ukrainian students in Polish schools - Agnieszka Koterwas; Edyta Nowosielska (Multidisciplinary Journal of School Education)
Research objectives (aims) and problem(s): The purpose of this article is to describe the experiences and strategies adopted by teachers and principals in response to the challenge of evaluating Ukrainian students. The research questions are as follows: What difficulties and obstacles do school teachers face in the process of assessing Ukrainian students? What strategies have teachers developed for evaluating these students?